3z+10z-86=2(5z-16)

Simple and best practice solution for 3z+10z-86=2(5z-16) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3z+10z-86=2(5z-16) equation:



3z+10z-86=2(5z-16)
We move all terms to the left:
3z+10z-86-(2(5z-16))=0
We add all the numbers together, and all the variables
13z-(2(5z-16))-86=0
We calculate terms in parentheses: -(2(5z-16)), so:
2(5z-16)
We multiply parentheses
10z-32
Back to the equation:
-(10z-32)
We get rid of parentheses
13z-10z+32-86=0
We add all the numbers together, and all the variables
3z-54=0
We move all terms containing z to the left, all other terms to the right
3z=54
z=54/3
z=18

See similar equations:

| 4y+7=5y-18 | | 8n+3=6n+13 | | -9=y/6-1 | | 7(v+2)=–14 | | –3q=36 | | 3/4(8x-4)-3x=12 | | 2p+69=4p-21 | | -12=8x-6x | | 14a+72=72 | | 4y+34+10y+2=64 | | 18b=–9(–2b+6) | | 32=20+z | | 3/5y-27=24 | | 4(5x-5)=100 | | 7n-23=-8(-5-2n) | | 48/80=n/3.5 | | 5r-21+3r=-7+2 | | (x+3)^(2)=4 | | 6(n)=3(n-1) | | 4(x-6)=(x-1) | | 5x-3=40(x=8)=-40 | | t3=–1 | | 4=7-3(1+2x) | | p+8=–3p | | 4+x+6x=40 | | 8(3a+7)-8a=26+6a | | 3b+2+5b-1= | | 5n+3=10n+23 | | 2.69(r+1)-5.91=2.16 | | 9x-17=-17+19x | | 8x6=(8x)=(8x) | | 3x^2+6x-3=87 |

Equations solver categories